Perlindungan Hukum bagi Masyarakat terhadap Keputusan Tata Usaha Negara yang Merugikan - Arif Effendi; Muhammad Fadhil Arfendi (MAMBA'UL 'ULUM, 2026)
State Administrative Decisions constitute an essential instrument in the administration of government. However, in practice, such decisions often result in adverse impacts on the public. Therefore, effective legal protection mechanisms are required to safeguard citizens’ rights. This article aims to analyze the forms of legal protection available to individuals against harmful administrative decisions and to evaluate their effectiveness within Indonesia’s administrative law system. This study employs a normative legal research method using statutory and conceptual approaches. The findings indicate that legal protection may be pursued through administrative remedies and judicial mechanisms; however, several challenges remain in their practical implementation.